Atomic fidelity of subunit-based chemically-synthesized antimalarial vaccine components (2010)
The tri-dimensional (3D) structure determined by NMR of functionally relevant High Activity Binding Peptides (HABPs) of chemically-synthesized malarial proteins, involved in invasion to target cells, is practically identical, at the atomic level, to their corresponding recombinantly produced proteins, determined by X-ray crystallography. Both recombinant proteins as well as these chemically-synthesized HABPs bind to host-cell receptors through channels or troughs formation, stabilized by hydrogen bonding; most of them are located on distant segments to the highly polymorphic, highly antigenic, strain specific amino acid sequences the parasite uses to evade immune pressure. When these immunologically silent conserved HABPs are specifically modified, they become highly immunogenic and capable of inducing protective immune responses, supporting the specifically modified minimal subunit-based, multiepitopic, chemically-synthesized vaccines concept. © 2009 Elsevier Ltd. All rights reserved.